Comparative Effects of Variations in Duodenal Glucose Load on Glycemic, Insulinemic, and Incretin Responses in Healthy Young and Older Subjects - Trahair, Laurence G.; Horowitz, Michael; Rayner, Christopher K.; Gentilcore, Diana; Lange, Kylie; Wishart, Judith M.; Jones, Karen L. (The journal of clinical endocrinology and metabolism, 2012)
Context:Aging is associated with deteriorating glucose tolerance. Studies assessing glucose tolerance and subsequent insulin and incretin hormone release often fail to take into account the rate of gastric emptying when evaluating these responses.Objective:Our objective was to determine the comparative effects of variations in the small intestinal glucose load on the glycemic, insulinemic, and incretin responses in healthy young and older subjects.Materials and Methods:Twelve healthy young (six males, six females; age 22.2 ± 2.3 yr) and 12 older (six males, six females; age 68.7 ± 1.0 yr) subjects had measurements of blood glucose, serum insulin and plasma incretin hormones [glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP)] and calculations of insulin resistance (homeostatic model assessment) and β-cell function corrected for insulin sensitivity, before and during intraduodenal infusions of glucose at 1, 2, or 3 kcal/min or saline for 60 minutes. The study was double-blinded and randomized, and performed in the Discipline of Medicine at the Royal Adelaide Hospital.Results:At baseline, blood glucose and serum insulin were slightly higher in the older subjects (P < 0.001), whereas GLP-1 and GIP were comparable between groups. In both groups, the glycemic, insulinemic, and GLP-1 responses were dependent on the duodenal glucose load in a nonlinear fashion (P < 0.001). The glycemic response was greater (P < 0.001) in the older subjects, whereas GLP-1 and GIP responses were comparable between groups. The older subjects were more insulin resistant (P < 0.001) and had impaired β-cell function, particularly at higher glucose loads (P < 0.05).Conclusion:When glucose is infused into the small intestine at equal rates in healthy young and older subjects, GLP-1 and GIP responses are comparable, indicating that impaired incretin secretion does not account for age-related glucose intolerance.